Integrating Disaster Response Tools for Clinical Leadership - Kenneth V. Iserson (Western Journal of Emergency Medicine)
Background: Disastrous situations in the emergency department (ED) or community can overwhelm even the best-prepared teams due to their complexity and dynamic nature. In this paper we propose an integrated approach to disaster management, combining six theoretical and practical frameworks to enhance decision-making and operational effectiveness. Discussion: The approach begins with “sensemaking,” an instinctive process that helps leaders quickly gain situational awareness, a crucial foundation for the recognition-primed decision process (RPD). RPD enables swift, experience-based decisions without exhaustive analysis, aligning them with the appropriate domain in the Cynefin framework to guide subsequent interventions. In chaotic situations, rapid action is necessary, and the edge-of-chaos theory guides leaders to balance order and chaos for optimal adaptability. Complexity theory aids in managing the unpredictable elements of a crisis, highlighting the need for flexible responses. Finally, the Incident Command System ensures effective implementation by providing a standardized approach to command, control, and coordination. This cohesive strategy equips emergency physicians and incident commanders to manage both internal ED crises and broader community disasters effectively, with an emphasis on the importance of training in these frameworks to enhance the resilience of emergency medical services. Conclusion: This multifaceted approach should improve disaster management by better preparing responders for the unpredictable nature of emergencies, enabling effective evaluation and management of complex scenarios, and leading to a more rapid restoration of order.